Single‐Chain Magnetic Behavior in a Hetero‐Tri‐Spin Complex Mediated by Supramolecular Interactions with TCNQF.− Radicals1. (11th September 2014) - Wang, Zhao‐Xi; Zhang, Xuan; Zhang, Yuan‐Zhu; Li, Ming‐Xing; Zhao, Hanhua; Andruh, Marius; Dunbar, Kim R.
Abstract The self‐assembly of organic TCNQF.− radicals (2‐fluoro‐7, 7, 8, 8‐tetracyano‐p‐quinodimethane) and the anisotropic [Tb(valpn)Cu]3+ dinuclear cations produced a single‐chain magnet (SCM) involving stacking interactions of TCNQF.− radicals (H2valpn is the Schiff base from the condensation of o‐vanillin with 1, 3‐diaminopropane). Static and dynamic magnetic characterizations reveal that the effective energy barrier for the reversal of the magnetization in this hetero‐tri‐spin SCM is significantly larger than the barrier of the isolated single‐molecule magnet based on the TbCu dinuclear core.